In vivo expansion of a CD9+ decidual-like NK cell subset following autologous hematopoietic stem cell transplantation - Ane Orrantia; Enrique Vázquez-De Luis; Gabirel Astarloa-Pando; Iñigo Terrén; Ainhoa Amarilla-Irusta; Diego Polanco-Alonso; Carmen González; Alasne Uranga; Tomás Carrascosa; Juan J. Mateos-Mazón; Juan C. García-Ruiz; Sergio Callejas; et al. (iScience, 2022)
Summary: Autologous hematopoietic stem cell transplantation (autoHSCT) is a treatment option for hematological disorders and pediatric solid tumors. After an autoHSCT, natural killer (NK) cells are the first lymphocyte subset returning to normal levels. To uncover global changes during NK cell reconstitution after autoHSCT, we performed RNA-sequencing on NK cells before and after autoHSCT. Results showed profound changes in the gene expression profile of NK cells immediately after autoHSCT. Several biological processes including cell cycle, DNA replication and the mevalonate pathway were enriched. Significantly, we observed that following autoHSCT, NK cells acquired a decidual-like gene expression profile, including the expression of CD9. By using multiparametric flow cytometry, we confirmed the expansion of NK cells expressing CD9 immediately after autoHSCT, which exhibited higher granzyme B and perforin expression levels than CD9− NK cells. These results provide insights into the physiopathology of NK cells during their reconstitution after autoHSCT.